Confidence Intervals for the Variance and the Ratio of Variances of Log-Normal Distribution with Known Coefficients of Variation - Niwitpong, Sa-aat (IJRDO -JOURNAL OF MATHEMATICS, 2016)
This paper presents the confidence interval for the variance and the ratio ofvariances of lognormal distribution with known coefficients of variation. Wederived analytic expressions to find the coverage probability and the expectedlength of the proposed confidence interval.